The behavioural aspects of financial literacy - Florian Gerth; Katia Lopez; Krishna Reddy; Vikash Ramiah; Damien Wallace; Glenn W. Muschert; Alex Frino; Leonie Jooste (Journal of Risk and Financial Management, 2021)
In this paper, we investigate the contribution of behavioural characteristics to the financial literacy of UAE residents after controlling for demographic factors. Specifically, we test the relationship between financial literacy and behavioural biases such as representativeness, self-serving, overconfidence, loss aversion, and hindsight bias. Using data collected through survey questionnaires, we apply the methodology developed by the Organization of Economic Co-operation and Development (OECD) to compute financial literacy scores. Our overall results show that all behavioural biases except for overconfidence bias are positively related to financial literacy. Furthermore, some biases exhibit a stronger quantitative relationship with financial literacy than others. For example, hindsight bias displays the strongest link to financial literacy, followed by self-serving bias. The weakest but still statistically significant effect is loss aversion bias. Although biases, in general, have negative connotations, behavioural biases appear to be related to higher levels of financial literacy.
Keywords: 330; behavioural finance; financial literacy; hindsight bias; loss aversion bias; overconfidence bias; representativeness bias; self-serving bias